Asistensi Kepelatihan Atlet Cabang Olahraga Gateball Jambi Menghadapi Kejunas 2025 dan Porprov Jambi 2026 - Putra, Anggrawan Janur; Simaremare, Tohap Pandapotan; Norito, Tri Bayu; Dinafi, Yusra; Kurniawan, Alexander (Jurnal Pengembangan dan Pengabdian Masyarakat, 2026)
Athlete training and development centers play a crucial role in achieving high sports performance, particularly in gateball, which requires well-planned and sustainable training programs. However, in Jambi Province, there are still challenges related to the application of sports science by coaches and the lack of an optimal training system to support the readiness of PERGATSI Jambi athletes in facing the 2025 National Gateball Championship and the 2026 Jambi Provincial Sports Week. The problem addressed in this activity is how to improve the effectiveness of training through the application of sports science by coaches and how coaching assistance can support the development of structured training programs, enhance athletes’ skills, and improve their mental readiness. To address these issues, a coaching assistance program was implemented using lectures, discussions, and sparring methods, including the preparation of training programs, mentoring during the training process, and evaluation of training outcomes. The results indicate an improvement in coaches’ understanding of sports science–based training planning, enhancement of athletes’ technical skills and mental readiness, and the development of more systematic and measurable training programs. The implication of this activity is an improvement in the overall quality of the training process and athlete preparedness, which is expected to contribute to better performance at both national and provincial competitions.